HARTA, TAHTA, WANITA DALAM PANDANGAN ISLAM - Abdurrasyid, Abdurrasyid (Jurnal Ilmiah Al-Hadi; Vol 4 No 1: Januari 2018DO - 10.54248/alhadi.v4i1.387, 2018)
Three types of temptations in the world that often make people complacent, namely property, thrones, and women. The Qur'an also explains the danger of these three temptations. Her alluring appeal does not infrequently make people forget the Lord so they easily fall and fall into a hole of humiliation. All three are forms of tests and trials; dazzling mirages that make people forget their main task in this world. If humans consider all three as a measure of the success of life, then be prepared to regret it in the afterlife. All of that is essentially a facility and loan from Allah SWT to be used to worship Him, not the final target of life. Especially if humans love him more than his love for Allah and His Messenger, then wait for the time when he is humiliated by Allah SWT before His creatures.